Introducing the addictive daydreaming scale: development and Polish validation of the ADS-20 and ADS-5 - Pietkiewicz, Igor J.; Hełka, Anna M.; Tomalski, Radosław (Frontiers in Psychiatry, 2025)
Background and aimsMaladaptive daydreaming (MD) is a pattern of excessive, compulsive fantasizing associated with functional impairment. While its classification remains debated, increasing evidence suggests that it may be understood as an addictive form of emotion regulation. This study aimed to develop and validate a new self-report tool, grounded in the behavioral addiction framework, for screening and assessing the severity of MD, and to examine its potential clinical utility.MethodsA mixed-clinical (N = 182) and non-clinical (N = 231) sample completed the Addictive Daydreaming Scale (ADS) in two forms: a 20-item full version (ADS-20) and a 5-item screening test (ADS-5), together with established measures of MD, quality of life, and self-rated impact of daydreaming.ResultsPsychometric analyses confirmed that both the ADS-20 and ADS-5 demonstrated high reliability and strong content, criterion, and construct validity. ADS scores were more strongly correlated with both the psychological and social domains of quality of life than Maladaptive Daydreaming Scale scores, supporting its sensitivity to functional impairment. Cut-off scores of ≥42 (ADS-20) and ≥8 (ADS-5) showed good accuracy for identifying clinically significant cases.ConclusionsThe ADS-20 and ADS-5 are reliable, valid instruments for identifying and assessing addictive features of maladaptive daydreaming. Their use may support improved clinical detection, assessing the severity of MD and help conceptualize it within the behavioral addictions framework.